Multi-level Governance in Environmental Risk Management - Petra Hiller (Oñati Socio-Legal Series)
The article examines regulatory strategies in the field of ecological disaster management with reference to the sociology of risk. The risk perspective draws attention to the fact that political strategies of regulation are to be understood as processes of risk transformation. The behavior of regulatory agencies is related to their perception of risks and opportunities. From this point of view, efforts in the field of disaster management appear as processes that turn perceived environmental threats into risks and opportunities for the agencies involved. The article shows the course of such a governance process which transforms environmental disasters into organizational risks and opportunities. This leads to the following research question: Which types of organizations favor strategies of risk avoidance and which organizations rather allow active pursuit of opportunities? The empirical part of this study is based on data obtained by field research in a multi-level negotiation system set up for managing hazardous wastes. Empirical findings support the assumption that organizational stability is a central condition for active pursuit of opportunities whereas organizational instability supports an orientation towards the avoidance of organizational risk.